METABOLIC SYNDROME AND THE DEVELOPMENT OF ATHEROSCLEROSIS (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2024)
According to the World Health Organization, about 60% of the world's population does not have enough physical activity to lead a healthy lifestyle (1,8).  As a result of a lifestyle caused by inactivity, 1.9 million deaths are observed in the literature.  Today, many sources provide information about the morphofunctional changes that occur in the body under the influence of the negative consequences of hypokinesia.  As a result of inactivity, negative consequences develop in all organs and systems (6,9). In the case of inactivity, changes such as negative changes in the respiratory system, impaired liver function, and decreased reproductive organs have been observed.  In the conditions of hypokinesia, a violation of carbohydrate metabolism, a change in the water-salt balance has been determined (2,3,5).  These metabolic changes involve many unsolved problems involving the same complex mechanisms in pathogenesis (4,7).